Association between Hyperhomocysteinemia and Diabetic Retinopathy - Ghazala Tabssum, Imran Ghayoor, Shabana Siddiqui (Pakistan Journal of Ophthalmology, 2018)
Purpose: To study the association between hyperhomocysteinemia (Hcy) and retinopathy among diabetics and non diabetics. Material and Methods: This Case control study was carried out at the department of Ophthalmology Liaquat National Hospital Karachi from March 2008 to November 2008. A total of 154 subjects were selected from Eye OPD, out of them 77 were diabetics with early retinopathy (cases) and 77 were non diabetics and had no history of ocular diseases (controls). Patients with advance proliferative DR were excluded. Sample size was calculated with the help of openepi software. Non probability purposive sampling was done. Results: Serum Hcy levels measured higher than 12 ?mol/L in 69 (85.2%) patients and lower than 12 ?mol/L in 8 (10.9%) patients with diabetes. While serum Hcy levels were lower than 12 ?mol/L in 65 (89.1%) patients and higher than 12 ?mol/L in 12 (14.8%) patients of control groups. Serum Hcy levels were significantly higher in DR patients than non diabetics. According to the findings, serum Hcy levels more than 12 ?mol/L were 47 times more frequent in diabetic patients with retinopathy than in non diabetics, with odds ratio of 46.71 (95% CI:17.95 to 121.6). Conclusion: A significant association was observed between hyperhomocysteinemia and DR, with chi square value of 46.79 and P value 0.0005 at the end of the study.